(untitled) (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2014)
Exemplary method in Islamic education is the most convincing method that has in fluenced to a great deal the success of character building of students such as moral, spiritual and social. Lack of role model among educatorsin practiceing Islamic values is seen as oneof the factor scontri buting to a moral crisis. Its applicationin Islamic educationis not only supported bye ducators, butalsoby the synergy between parentsand theen vironment. Exemplarymodels demonstrated by the educators, parentsandcommunity,consciously ornot, areattached tothemselves, eitherin their speeches, deeds, andother material and spiritual things. Educatorsmust beable toact asrole modelsfortheir students, as well as parentsfor their children. And all people can bea good examplein their life.